2021
DOI: 10.1093/mnras/stab3049
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of precession on the observed population of ULXs

Abstract: The discovery of neutron stars powering several ultraluminous X-ray sources (ULXs) raises important questions about the nature of the underlying population. In this paper we build on previous work studying simulated populations by incorporating a model where the emission originates from a precessing, geometrically beamed wind-cone, created by a super-critical inflow. We obtain estimates – independent of the prescription for the precession period of the wind – for the relative number of ULXs that are potentiall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 89 publications
(140 reference statements)
2
5
0
Order By: Relevance
“…This behavior is similar to that seen in the long-term X-ray flux variations of ULX pulsar NGC 7793 P13 (Fürst et al 2021). For both ULX-1 and NGC 7793 P13, the authors conjectured that this behavior was due to obscuration of the pulsar, possibly due to an outflow (Kosec et al 2018) or Lense-Thirring precession of the inner accretion disk (Middleton et al 2018(Middleton et al , 2019Khan et al 2022). This supported the work by Carpano et al (2018), who found a large difference in absorption column density between X-ray observations in 2010 (XMM-Newton) and 2016 (XMM-Newton and NuS-TAR), while keeping other spectral parameters tied.…”
Section: Introductionsupporting
confidence: 72%
“…This behavior is similar to that seen in the long-term X-ray flux variations of ULX pulsar NGC 7793 P13 (Fürst et al 2021). For both ULX-1 and NGC 7793 P13, the authors conjectured that this behavior was due to obscuration of the pulsar, possibly due to an outflow (Kosec et al 2018) or Lense-Thirring precession of the inner accretion disk (Middleton et al 2018(Middleton et al , 2019Khan et al 2022). This supported the work by Carpano et al (2018), who found a large difference in absorption column density between X-ray observations in 2010 (XMM-Newton) and 2016 (XMM-Newton and NuS-TAR), while keeping other spectral parameters tied.…”
Section: Introductionsupporting
confidence: 72%
“…This behavior is similar to that seen in the long-term X-ray flux variations of ULX pulsar NGC 7793 P13 (Fürst et al 2021). For both ULX-1 and NGC 7793 P13, the authors conjectured that this behavior was due to obscuration of the pulsar possibly due to an outflow (Kosec et al 2018) or Lense-Thirring precession of the inner accretion disk (Middleton et al 2018(Middleton et al , 2019Khan et al 2022). This supported the work by Carpano et al (2018), who found a large difference in absorption column density between X-ray observations in 2010 (XMM-Newton) and 2016 (XMM-Newton and NuSTAR), while keeping other spectral parameters tied.…”
Section: Introductionsupporting
confidence: 72%
“…XLFs can also be directly compared with population synthesis calculations which include the evolution of systems through their various phases (including mass transfer, common envelope, SNe and gravitational inspiral). Recent attempts include those by Wiktorowicz et al (2019) where the effect of geometrical beaming (following equation 55) is included, Khan et al (2021), where the observational impact of precession is considered (see below), and Kuranov et al (2020) who obtain the XLF for magnetised neutron stars in the absence of beaming and precession of the wind-cone (see section 2.3.3).…”
Section: Catalogues and X-ray Surveysmentioning
confidence: 99%